2012
DOI: 10.1590/s0004-27302012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subclinical hypothyroidism treatment on psychiatric symptoms, muscular complaints, and quality of life

Abstract: Objectives:To evaluate the impact of subclinical hypothyroidism (sHT) treatment on health--related quality of life (QoL), psychiatric symptoms, clinical score, and muscle function. Materials and methods: In this randomized double-blind study, patients were assigned either to treatment (n = 35) or placebo (n = 36). Clinical and psychiatric symptoms were assessed by the Zulewski, Hamilton and Beck scales. QoL was assessed by the SF-36 questionnaire. Assessments of quadriceps (QS) and inspiratory muscle (IS) stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 36 publications
3
49
0
1
Order By: Relevance
“…Neurobiological evidence seems to corroborate the hypothesis of an organic basis of the effects of thyroid hormone on the brain and on psychiatric symptoms [9]. …”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Neurobiological evidence seems to corroborate the hypothesis of an organic basis of the effects of thyroid hormone on the brain and on psychiatric symptoms [9]. …”
Section: Introductionmentioning
confidence: 84%
“…There are very few studies that evaluated HRQoL in sHT [9, 10], and none included cardiorespiratory fitness and health status in the same study. It is believed that some psychological aspects of thyroid hypofunction, when present in sHT, may be influenced by physical findings, as suggested by the association between physical aspects of quality of life, in the SF-12 evaluation and cardiorespiratory fitness, specially VO 2max⁡ , in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simonsick and co-workers [147], in a small sample of patients found no difference in gait speed decline between patients with Shypot undergoing replacement therapy or without any treatment. Recently, Reuters and colleagues [217] performed a randomized double-blind study, in which adults with Shypot were assigned either to treatment (n=35) or placebo (n=36). The Authors showed an improvement of inspiratory muscle strength in the treatment arm, along with an improved quality of life.…”
Section: Hormonal Therapeutic Strategies To Improve Mobilitymentioning
confidence: 99%
“…Symptoms and signs of hypothyroidism have been frequently found in subclinical hypothyroidism patients, as reported by many authors. In fact, Reuters et al described an improvement in some physical aspects of quality of life after L-T4 treatment in patients with subclinical hypothyroidism [50].…”
Section: Subclinical Hypothyroidismmentioning
confidence: 99%